The Indian in the cupboard - BANKS, LYNNE REID (b)
The Indian in the Cupboard by Lynne Reid Banks is a classic fantasy novel about Omri, a young boy who receives a plastic Indian figurine and an old cupboard for his birthday. When he locks the toy inside with a special key, it comes to life as a living, breathing Iroquois man named Little Bear.
English